2011
DOI: 10.1007/s10452-011-9375-7
|View full text |Cite
|
Sign up to set email alerts
|

Physiological indicators of fitness in benthic invertebrates: a useful measure for ecological health assessment and experimental ecology

Abstract: Physiological indicators of fitness present a measure of an organism's response to a changing environment. An analysis of how these organisms allocate and store their energy resources provides an understanding of how they cope with such environmental changes. Each individual has to balance the investment necessary to acquire a certain resource with the energy gained by it. This trade-off can be monitored by measuring several physiological indicators of fitness such as energy storage components, metabolic state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 78 publications
(97 reference statements)
2
35
0
Order By: Relevance
“…Hence, we deduced a NOEC TG of 0.03 µg l −1 (0.06 µg l −1 nominal) and a LOEC TG of 0.21 µg l −1 (0.6 µg l −1 nominal) for an indirect effect of terbutryn on the physiological condition of grazers. This result underlines the high sensitivity of this endpoint to environmental changes and supports the view that it might be a good measure for subtle effects of biotic and abiotic factors in further laboratory and environmental studies (Koop et al 2011).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Hence, we deduced a NOEC TG of 0.03 µg l −1 (0.06 µg l −1 nominal) and a LOEC TG of 0.21 µg l −1 (0.6 µg l −1 nominal) for an indirect effect of terbutryn on the physiological condition of grazers. This result underlines the high sensitivity of this endpoint to environmental changes and supports the view that it might be a good measure for subtle effects of biotic and abiotic factors in further laboratory and environmental studies (Koop et al 2011).…”
Section: Discussionsupporting
confidence: 76%
“…Also, the direct comparison of absolute triglyceride levels between the terbutryn experiment and the emergence experiment would not be meaningful, due to the different life stages used (larvae vs. adults) and the accompanying differing triglyceride levels (Cargill et al 1985, Servia et al 2006, Winkelmann & Koop 2007). However, a reduction of triglycerides of about 24% is still a clear indication of a reduced energy uptake; especially considering that triglycerides are the major energy store of mayflies and, hence, the main indicator of physiological fitness (Koop et al 2011), as shown for Rhithrogena semicolorata, Ephemera danica (Winkelmann & Koop 2007) and Heptagenia flava .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, since gammarids require lipids for reproduction (Glazier, 2000;Plaistow et al, 2003), the observed lower lipid content may be indicative for a lower reproductive capacity (Koop et al, 2011), which may finally result in a lower abundance and in consequence lower contribution of Gammarus to local leaf breakdown.…”
Section: Implications For Stream Energy Flowmentioning
confidence: 99%
“…The rRNA:rDNA ratio is then an index of the growth rate for a particular taxon classified by its 16S rRNA gene sequence. RNA content is also used in ecological studies of fish and invertebrates (Ciotti et al 2010, Koop et al 2011.…”
Section: Potential Growth Rates Of Individual Bacterial Taxamentioning
confidence: 99%